Angry laughter: Postcolonial representations of dictatorial masculinities. (1st December 2019) - Baker, Charlotte
AbstractFocusing on the representation of the masculinity of dictator figures in Cheik Aliou Ndao's Mbaam dictateur (1997) and Baba Galleh Jallow's Angry Laughter (2004), this article explores the imbrication of social realities, power structures and literary expression that characterizes these texts as dictator-novels. It considers the writers' reappropriation of the border between animal and human as a means by which to level an allegorical political critique in the guise of a fable. In so doing, it emphasizes their representation of the hypermasculine body of the dictator and its centrality to emerging nation states that are defined by class and ethnic relations. Finally, its focus turns to the importance of voice to examine the aesthetic of these two dictator-novels, which is of equal importance to our understanding of these texts as their thematic representation. The article thus takes these two literary works as case studies for the dictator-novel at the turn of the twenty-first century to examine the ways in which African writers use the dictator-novel to express the disenchantment of citizens with the long and faltering process of decolonization that, in many countries across Africa, had seen the emergence not of an ideal postcolonial democracy, but instead of a de-humanizing neo-colonial autocracy.